Cerebral cavernomatosis and epilepsy: treatment and serial imaging follow-up - Catalina Elena Bistriceanu; Dan Iulian Cuciureanu (Romanian Journal of Neurology, 2023)
Cerebral malformations, known as cavernomas, are low flow vascular malformations that have a multilobulated appearance. A large percent of cavernous malformations have seizures as initial symptoms. We report a case of a 48 years old patient presented in the neurological department for seizure work-up. We performed serial brain imaging to follow the evolution of bleeding cavernomas and electroencephalography to find epileptogenic cavernomas. Conservative management was decided and the evolution under antiepileptic drugs was good, but with some compliance issues further discussed.